Staphylococcus aureus and S. epidermidis in biological systems of hospital environment: Antibiotic resistance patterns in regions of Ukraine - Berezhna, A. V.; Tertyshnyi, V. O.; Makarova, V. I.; Chumachenko, T. O. (Regulatory Mechanisms in Biosystems, 2021)
Staphylococcus bacteria are ubiquitous and often circulate in the biological systems of the hospital environment. Staphylococci have developed antibiotic resistance mechanisms resulting in a significant medical and economic burden to the healthcare system. The goal of our research was to conduct a comparative analysis of resistance to antibiotics in S. aureus and S. epidermidis isolates found in surgical hospitals in Kharkiv and Poltava regions. In 2013 through 2019, 151,015 and 98,754 tests were made by disc-diffusion method to identify the sensitivity in the S. aureus strains to antibiotics in Kharkiv and Poltava regions respectively. In 2013–2015, 15,589 tests were made in Kharkiv region to identify antibiotics sensitivity in S. epidermidis strains. Comparison of antibiotic resistance of the S. aureus strains in Kharkiv and Poltava regions was performed using the Pearson Chi-square test (χ2) and Fisher’s exact test. The proportion of S. aureus strains resistant to penicillins, cephalosporins, carbapenems, aminoglycosides, and macrolides was higher in Kharkiv region in terms of statistical validity than in Poltava region. Overall, the proportion of S. aureus strains resistant to lincozamids, tetracycline antibiotics, and fluoroquinolones in Poltava region was higher in terms of statistical validity than in Kharkiv region. An analysis of resistance of S. aureus strains to linezolid demonstrated that in Poltava region the proportion of resistant microorganisms was higher in terms of statistical validity in 2013–2014 and in 2016–2018. In Kharkiv region, in 2013 and in 2014, 96.3% and 89.1% of isolated strains of S. aureus respectively, were resistant to vancomycin. In 2019, more than a quarter of the located isolates (26.6%) in Poltava region were resistant to this antibiotic. The analysis of the dynamic of resistance in S. epidermidis isolates demonstrated that in 2015 nearly half of the isolates located in Kharkiv region were insensitive to penicillin antibiotics. Between 2013 and 2015, the spread of resistance to cephalosporins, aminoglycosides, macrolides, and fluoroquinolones among the S. epidermidis isolates noticeably increased. When S. epidermidis resistance to vancomycin was analyzed, a decrease in the proportion of resistant strains from 88.0% in 2013 to 8.7% in 2015 was noted. A promising direction for further research is the creation of passports of microorganism resistance in the regions and various health-care settings, as well as the creation of a unified national database network on microorganism resistance using modern methodologies for determining the phenotypes and genotypes of microorganisms.